Studies on Schismatoglottideae (Araceae) of Borneo XXIX - Piptospatha manduensis-The Ultimate aroid calciphile ? - Boyce, P.C; Wong, Sin Yeng (International Aroid Society Inc., 2013)
Piptospatha manduensis A. Hay & Bogner is highlighted as a truly calciphilous aroid obligated to travertine in north eastern Indonesian Borneo. Based on new collections and cultivated plants an updated description is offered. A brief overview of the other very few calciphilous aroids in Borneo is presented, and together with P. manduensis, all are illustrated.